Potential of Tropical Seaweed Carageenan in Applications of Soft Capsule as a Replacement for Gelatin: A Review - Hidayat, Taufik; Syamsu, Khaswar; Sunarti, Titi Candra; Nurilmala, Mala; Manalu, Lamhot (Science and Technology Indonesia, 2025)
Carrageenan, a natural sulfated polysaccharide extracted from red seaweed, has gained significant attention in the development of drug delivery systems, particularly as a capsule-forming material. With its biodegradable, biocompatible, and gel-forming properties, carrageenan offers great potential as a plant-based alternative to animal-derived gelatin. This review evaluates the potential of carrageenan, especially iota-carrageenan, in the production of soft capsules as a gelatin substitute, and compares the characteristics of carrageenan-based hard and soft capsules. Soft capsules are generally formulated with iota-carrageenan and plasticizers such as glycerol to achieve optimal flexibility, while hard capsules utilize kappa-carrageenan due to its stronger gel texture. Structural modifications, including depolymerization and polymer blending, have been reported to improve viscosity, elasticity, and disintegration time of carrageenan capsules. Nevertheless, limitations remain, such as high viscosity and slower disintegration compared to gelatin-based capsules. Therefore, formulation optimization and advanced extraction techniques are essential to enhance carrageenan capsule performance. Future research should emphasize cost-effective and high-purity extraction methods, engineered depolymerization processes, and the modification of kappa-carrageenan to exhibit iota-like flexibility. These strategies are expected to advance the feasibility of tropical seaweed-derived carrageenan as a sustainable and halal-compliant material for pharmaceutical capsule applications.